Bioaccessibility of Airborne Particulate-Bound Trace Elements in Shanghai and Health Risk Assessment - Huang, Xian; Cheng, Jinping; Bo, Dandan; Betha, Raghu; Balasubramanian, Rajasekhar (Frontiers in Environmental Science, 2016)
Increased concentrations of airborne particulate matter in megacities within China, caused by rapid economic growth, urbanization and industrialization, have become a major health concern. High energy consumption, emissions from a large fleet of on-road vehicles and intense industrial activities all contributed to the deterioration of urban air quality in China. In this study, we investigated the bioaccessibility of twelve particulate-bound trace elements (Al, Co, Cd, Cr, Cu, Fe, K, Mg, Mn, Ni, Pb, and Zn) using simulated lung fluids (Gamble’s solution (pH = 7.4) and artificial lysosomal fluid (ALF) (pH = 4.5)) following the collection of PM in Shanghai, a megacity in China, to gain a better understanding of their fate upon inhalation by adults and children. All the trace elements showed higher bioaccessibility in ALF, compared to that in the Gamble’s solution, due to lower pH and higher ionic strength of the former over the latter. In most cases, the kinetic response of trace elements in terms of their solubility followed a curvilinear pattern and approached near steady-state characteristics after a protracted period of incubation in the lung fluids. Health risk assessment was conducted for adults and children based on the measured bioaccessible fractions of trace elements, which showed significant excess lifetime cancer risk to both children and adults.